Prevalence of Midwakh tobacco smoking in trend-setting Lebanon: an indicator of potential spread across the Arab world? - Rima Afifi; Lilian Ghandour; Noura El Salibi; Rima Nakkash; Alissar Rady; Scott Sherman (Tobacco Induced Diseases, 2018)
Background Alternative tobacco product (ATP) use is increasing in Lebanon. Dokha (or 'diziness') is an ATP smoked in a pipe called a midwakh. Research evidence suggests high nicotine content, with resultant physiologic effects. The objective of this study was to assess prevalence and correlates of midwakh tobacco use among 7 th -12 th grade students in Lebanon.